The Continuing of Traditions: On the III National Scientific-Practical Conference with International Participation to the 110th Anniversary of Susanna Rubinstein - Zvereva N.V.; Roschina I.F.; Hromov A.I. (Клиническая и специальная психология, 2021)
The article is devoted to the traditional conference on clinical psychology held on November 25-26, 2021 in Moscow for the third time. The Conference was dedicated in the memory of Susanna Yakovlevna Rubinstein. A hybrid format of the conference is described, a wide geography of participants from Russia and abroad is shown, detailed topics of the plenary and breakout sessions, as well as workshops are presented.